The proportion of fine particles in pelleted diets does not affect performance of slow-growing broiler chicks - Fabiana Ramos-Santos (Universidad de Antioquia, 2020)
Background: The slow-growing chicken strains have particular nutritional and digestive needs, so they may digest pelleted feeds differently compared to commercial strains. Objective: To evaluate performance, digestibility, serum biochemical profile, digestive morphometry, carcass and cut yields of slow-growing broiler chickens fed pelleted feed with different concentrations of fine particles. Methods: A total of 180 slow-growing broiler chicks (Isa Label strain) aged one day were used. The animals were distributed in a completely randomized design with a 2 x 3 factorial scheme (Sex: male or female; Proportion of fine particles: 0, 50, or 100%), with six repetitions of five birds/cage. The birds received water and feed ad libitum during the 28-day experimental period. Results: The proportion of fine particles did not affect the metabolic, digestive or productive variables evaluated. Males showed better overall performance, while females produced better thigh and liver yields. Conclusion: The proportion of fine particles in pelleted feeds did not affect productive or metabolic parameters. Thus, improving pellet quality for slow-growing broilers during the initial rearing phase may not be justified.